Brace, Amanda. Ghost story from Victoria Street, St. John's. - Jarvis, Dale Gilbert, 1971- (2011)
Recording of a ghost story told by Amanda Brace, a Grade 8 student at St. Peter's Junior High. Recorded in the Newman Wine Vaults Provincial Historic Site as part of the Young Folklorists Program run by the Heritage Foundation of Newfoundland and Labrador in May, 2011. Amanda writes, "The story I chose takes place in downtown St. John's. I came across it doing my heritage fair project on folklore. The story is called 'The Haunted House of Victoria and Bond' and is about a young couple moving back from America and the fright they get the first night they moved."